Advanced Materials in Industrial and Environmental Engineering : Selected, peer-reviewed papers from the Conference Nanophysics and Nanomaterials (NaN), on November 27-28, 2019, St. Petersburg, Russia - Syrkov, Andrey G.; Pryakhin, Evgeniy I.; Maksarov, Vyachelsav V.; Martyushev, Nikita V. (Trans Tech Publications Ltd, 2020)
The volume contains papers presented at the Conference Nanophysics and Nanomaterials (St Petersburg, Russia, on 27-28 November 2019). This collection discusses advances in the area of structural materials, nanomaterials and nanotechnologies, metallurgical technologies, coatings and surface engineering, functional materials, minerals and industrial waste processing, materials for biomedical application. Steel, Alloys, Metallurgy, Processing Technologies, Microstructure, Mechanical Properties, Composites, Nanopowder, Nanomaterials, Ceramics, Functional Materials, Semiconductors, Fullerene, Thin Films, Coatings, Surface Treatment, Microanalysis, Minerals, Waste Processing, Hydroxyapatite, Nanosized Phosphor, Modelling, Computational Analysis Materials Science, Building Materials, Mechanical Engineering.
Keywords: Nanostructured materials -- Congresses.; elektronické knihy; electronic books